Political influences and investors’ perceived risk: a preliminary study - Rusli M. N.,; Mamat N. J. Z.,; Mohd Suradi N. R.,; Mustafa Z.,; Zalina Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The objective of the study is to discuss the effects of political influence on investors’ perceived risk under the political connected firms. Under the Malaysian political environment, relationship based of economic system which commonly practiced by most of the listed firms would enhance the needs of politician to participate as directors of the firm in order to ensure the firm’s survival in competitive industry. The effects of systematic exchange of favours between politician and firms has led to the arguments of political hypotheses in governance literature. As supported under the helping hand effects, empirical evidences have shown a favourable impact on firms accounting value and market based-performance due to the government favours and bailed-out to connected firms. However, the government obligations towards the people in social and political agenda have exacerbated the rent-seeking activities of political directors in realising the objectives. Moreover, due to the increasing number of cases reported involving high political figures in allegations of misallocation of firm’s resources and abuse of power in the 1MDB (1Malaysia Development Berhad), manipulation of stock figures and forgery of signatures of board members for a numbers of transactions in FGV (Felda Global Ventures Holdings Berhad), the credibility of politicians to perform his duties as firms’ director to maximising the shareholders’ wealth is questioned. As a consequence, a negative perception on the government may lead to inefficient capital market thus impair the investors’ confidence in future investment.